Uso das lectinas de algas marinhas no diagnóstico de Diabetes Mellitus e em atividades antinociceptiva e antiedematogênica - Rocha, Maria Luiziete Alves da (2006)
The red seaweeds Amansia multifida (AM), Bryothamnion triquetrum (BT) and Meristiella echinocarpa (ME), had been collected in reefs of tide in the beach of Flexeiras, City of Trairí, State of Ceará. For the development of the work the lectins of these seaweed had been isolated and compared about the hemagglutination activity against erythrocytes of individuals with diabetes mellitus type 1 (DM1), type 2 (DM2) and healthy indviduals with normal sugar level. [...]